Recent advances in pig reproduction: Focus on impact of genetic selection for female fertility. (21st September 2018) - Kemp, Bas; Da Silva, Carolina L. A.; Soede, Nicoline M.
Contents: In the past 30 years, sows have been successfully selected for a shorter weaning‐to‐oestrus interval and increased litter size. This review discusses the consequences of this selection for the reproductive physiology of sows, including the consequences for litter characteristics at birth. It also discusses breeding and management opportunities to deal with this changed genetics.